2020
DOI: 10.1177/0145561320922097
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Values of Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, and Other Prognostic Factors in Pediatric Patients With Bell’s Palsy

Abstract: Background and Objectives: Bell’s palsy (BP) is the most frequent cause of unilateral facial paralysis, and inflammation is believed to play an important role in pathogenesis. Due to its rarity, however, no consensus has been reached regarding optimum treatment or factors affecting prognosis. In the present study, treatment outcomes and prognostic factors of BP were investigated in pediatric patients who underwent steroid therapy. The goal was to investigate the relationship between BP and inflammation using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Therefore, PLR becomes available as one of the markers of inflammatory events and a marker of mortality 23,27 . Kim et al concluded that NLR and PLR values were higher in the group with Bell's palsy compared to the control group and this was rumoured to be associated with inflammation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PLR becomes available as one of the markers of inflammatory events and a marker of mortality 23,27 . Kim et al concluded that NLR and PLR values were higher in the group with Bell's palsy compared to the control group and this was rumoured to be associated with inflammation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The median clinical recovery time was 10 (3-90) days. The median clinical recovery time was 30 (10-90) days in boys and 7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) days in girls, and the clinical recovery time was longer in boys (p=0.032). The hemogram parameters (leukocyte count, platelet count, neutrophil-lymphocytemonocyte percentage, RBC, Htc, Hb, MCV, RDW, MPV, NLR, MLR and PLR) of patients with Bell's palsy were similar to Lymphocytes direct immune system activity.…”
Section: Resultsmentioning
confidence: 97%
“… 13 Studies have shown that in patients with idiopathic facial nerve palsy, higher levels of NLR are associated with more severe facial nerve palsy symptoms and longer recovery time. 30 However, although other research shows no significant difference in NLR levels between patients with differing prognoses. 31 Therefore, the relationship between NLR and idiopathic facial nerve palsy remains controversial.…”
Section: Discussionmentioning
confidence: 93%